Samopodoba in učenje izvajanja dihalnih vaj pri mladih športnih plezalcih - Hohkraut, Mateja (Šport (Ljubljana), 2017)
The basic purpose of the research was to teach young sport climbers the correct performance of breathing exercises and determine whether there is a correlation between their measured self-confidence and learning skills. Furthermore there was an examination of the effects the 10-week-long performance of breathing exercises caused to one's self-confidence. There were 14 kids included in the research. The datas were collected through the interview and also two questionnaires were used - the SPA questionnaire for measuring self-confidence and the questionnaire for measuring only self-confidence related to the trainings and competitions. The data analysis were made with the SPSS 17.0 statistical program, where descriptive statistics (mean, standard deviation), a T-test for related samples and Pearson's coefficient were used. Young sport climbers successfully learned the breathing exercises and the results showed improvements in 2 components of self-confidence (emotional and physical) after 10 weeks of performing exercises. There were no connections among the following variables: self-confidence and learing skills, self-confidence and gender and the general self-confidence and confidence, related to trainings and competitions, although the differences between boys and girls were noticable.
Keywords: breathing exercises; dihalne vaje; learning; relaxing; samopodoba; self-confidence; sport; sport climbing; sproščanje; šport; športno plezanje; učenje